Enhancing Audio Description: Inclusive Cinematic Experiences Through Sound Design - Lopez, Mariana; Kearney, Gavin; Hofstadter, Krisztian (Journal of Audiovisual Translation, 2021)
This paper explores the creation of an alternative to traditional Audio Description for visually impaired film and television audiences. The Enhanced Audio Description (EAD) methods utilise sound design as the main vehicle for accessibility and advocate for the integration of accessibility practices to filmmaking workflows. Moreover, this integrated strategy results in an organic form of accessibility that can cater for both visually impaired and sighted audiences, championing inclusive cinematic experiences. The present article reflects on the discussions held during focus groups in which mixed audiences of visually impaired and sighted people watched the same film, with the same EAD soundtrack over headphones. The discussions highlight the potential of the format as an example of universal design and accessible filmmaking, which can be enjoyed regardless of audience’s sight condition and can be offered alongside traditional Audio Description (AD) in order to cater for different aesthetic preferences. Lay summary Audio Description (AD) is a third person commentary added to film and television productions to make them accessible for visually impaired audiences. Traditionally, AD is added to productions after they have been completed, meaning that the creative and accessibility teams do not work together to produce the accessible version of the production. This paper explores an alternative to traditional AD, called Enhanced Audio Description (EAD), whose methods are integrated to filmmaking workflows. EAD moves away from a focus on verbal descriptions and instead focuses on sound design strategies. In EAD the traditional third person commentary is replaced by the combination of three techniques. The first is the addition of sound effects to provide information on actions, convey abstract scenes as well as indicate time, place, and the presence of characters. The second is the use of binaural audio (3D audio over headphones) to convey the position of characters and objects portrayed on the screen. Finally, first-person narration is used to portray feelings, gestures, colours as well as certain actions. The application of EAD methods results in a form of accessibility that can cater for both visually impaired and sighted audiences, championing inclusive cinematic experiences. Focus groups with audiences of visually impaired and sighted people demonstrated the potential of the format to be widely enjoyed, and to be offered alongside traditional Audio Description (AD) in order to provide accessible experiences which cater for different aesthetic preferences.